PERANCANGAN BUKU UNTUK MEMBANTU DALAM MENGGAMBAR UNTUK REMAJ - Bagus Widhi Nugraha; Shienny Megawati Sutanto (Universitas Ciputra Surabaya, 2020)
Illustration have a role on the life of the people, because of that athe interest on illustration has gradually increase. A lot of people wanted to learn on how a drawing is made. One of the way for them to learn is by looking for a tutorial book that have information on the basic of drawing. The purpose of this research is to get the understanding of how to construct a drawing tutorial book which interesting, and also able to help develop the drawing skill of teenager. The research method in collection data done by using the premier and secondary method. Primer method used qualitative used by doing an interview with expert and extreme user, while Quantitative used by spreading quisionare to 50 market candidate. Secondary research method used by researching literary work and journal. The result of the research is developing a book that visually interesting and easy to understand, also provide suggestion and a method for teen to be able to develop more of their drawing skill autonomously. Keyword : Drawing book, Illustration, Manga, Tutorial, Method.